Childhood Obesity and Breastfeeding Rates in Pennsylvania Counties—Spatial Analysis of the Lactation Support Landscape - Blair, Anna; MacGregor, Ellie; Lee, Nikki (Frontiers in Public Health, 2020)
Childhood obesity is a global public health issue. As the prevalence of childhood obesity continues to rise, identification of potential interventions by public health policy makers, and health care providers is imperative. Breastfeeding, the most optimal method of infant feeding, has been demonstrated to protect against childhood obesity. Lactation support providers (LSPs) play a key role in providing education, care, and support to families considering a feeding choice. Access to professional lactation care increases breastfeeding initiation, exclusivity, and duration rates, regardless of the credential that the LSP holds. The aims of the current study were to examine the relationship between childhood obesity and breastfeeding rates in Pennsylvania (PA) counties; to examine the relationship between geographic access to professional LSPs in PA counties and breastfeeding rates; and to examine the relationship between geographic access to professional LSPs and childhood obesity in PA counties. Data were collected on 617 professional LSPs in 67 PA counties. There are 608 Certified Lactation Counselors (CLCs) and 144 International Board Certified Lactation Consultants (IBCLCs) in PA. County-level breastfeeding rates, childhood obesity rates, and the number of CLCs and IBCLCs were tested for significance at the p < 0.01 level using a two-tailed significance test and bivariate Pearson's correlation. The results show a significant, inverse relationship between breastfeeding rates and childhood obesity prevalence at the county level, p < 0.01. There is also a significant, inverse relationship between the number of CLCs and the number of all professional LSPs and childhood obesity rates at the county level, p < 0.01. Thus, the availability of breastfeeding support is significantly related to breastfeeding rates and inversely related to childhood obesity rates across Pennsylvania.